Utilizing CodeIgniter 3 Framework in the Development of an Online Beverage Sales Platform - Hidayatulloh, Muhamad; Munawir, Ahmad; Rohman, Ali (PT Mattawang Mediatama Solution, 2025)
Web-based information systems have become an effective solution to enhance efficiency and accuracy in online sales transactions, including in the beverage business such as Es Teh Indonesia. This study aims to design and develop a web-based ordering information system using the CodeIgniter 3 framework to simplify the ordering process and manage data related to products, brands, categories, and transaction reports. The methodology used in this study is the waterfall method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system design includes user interfaces (UI) for both customers and administrators, as well as UML diagrams such as use case, activity, and sequence diagrams. The developed system is capable of handling login, user registration, product selection, order form submission, checkout, and order confirmation processes. On the admin side, the system provides features to manage brand, category, and product data, as well as generate transaction reports based on a specific date range. The results of testing using the black box method indicate that all functions perform as expected. In conclusion, this web-based information system successfully improves the convenience and efficiency of the ordering process and business data management at Es Teh Indonesia, while also enhancing service speed and accuracy for customers.